Death in the air : a novel [large type] - Murali, Ram (HarperCollins Publishers, 2024)
The White Lotus meets Knives Out meets Crazy Rich Asians in this devilishly entertaining debut novel: both a sophisticated locked-room mystery in the tradition of Agatha Christie, and a provocative literary whodunit for the twenty-first century. Ro Krishna is the American son of Indian parents, educated at the finest institutions, equally at home in London’s poshest clubs and on the squash court, but unmoored after he is dramatically forced to leave a high-profile job under mysterious circumstances. He decides it’s time to check in for some much-needed R&R at Samsara, a world-class spa for the global cosmopolitan elite nestled in the foothills of the Indian Himalayas. A person could be spiritually reborn in a place like this. Even a very rich person. But a person - or several - could also die there. Samsara is the Sanskrit word for the karmic cycle of death and rebirth, after all. And as it turns out, the colorful cast of characters Ro meets - including a misanthropic politician; an American movie star preparing for his Bollywood crossover debut; a beautiful heiress to a family jewel fortune that barely survived Partition; and a bumbling white yogi inexplicably there to teach meditation - harbors a murderer among them. Maybe more than one. As the death toll rises, Ro, a lawyer by training and a sleuth by circumstance, becomes embroiled in a vicious world under a gilded surface, where nothing is quite what it seems . . . including Ro himself.